Integration of 18-FDG PET/CT in the Initial Work-Up to Stage Head and Neck Cancer: Prognostic Significance and Impact on Therapeutic Decision Making - Leclere, Jean-Christophe; Delcroix, Olivier; Rousset, Jean; Valette, Gerald; Robin, Philippe; Guezennec, Catherine; Le Pennec, Romain; Gujral, Dorothy M.; Abgral, Maelig; Ollivier, Luc; Marianowski, Remi; Salaun, Pierre-Yves; et al. (Frontiers in Medicine, 2020)
Background The objective of this study was to assess the therapeutic and prognostic impact of integrating18F-fluorodeoxyglucose (18-FDG) positron emission tomography (PET) / computed tomography (CT) into work-up (WU) at initial staging of patients with head and neck squamous cell carcinoma (HNSCC). Method 477 consecutive patients (414M/63F, mean age 62.3 ± 9.7 years) with newly diagnosed HNSCC who underwent pre-treatment 18-FDG PET/CT were retrospectively included. The 18-FDG PET/CT stage (sPET) was compared to the conventional work-up stage (sCWU). A group of cancer specialists determined whether integrating PET/CT into WU at initial staging had an impact on the therapeutic decision, classifying the clinical impact as high (change in therapeutic modality), medium (change in the radiotherapy or surgical procedure) or low (modification of TNM staging and/or detection of synchronous cancer without high or medium impact). Three-year overall survival (OS) was considered as primary endpoint of the prognostic analysis. Results 18-FDG PET/CT had a clinical impact in 221 patients (46.3%) with a medium or high impact on management in 94 (19.5%) patients. Medium and high impact of 18-FDG PET/CT was statistically equivalent between sCWU-stage I/II and III/IV subgroups (p=0.02). 42 patients were PET/CT-upstaged from early stage I/II to advanced stage III/IV and had a significantly lower 3-year OS than those with concordant CWU and 18-FDG PET/CT early stage (54.8% vs. 82.6%, p=0.001). Conclusion This study demonstrated that implementing 18-FDG PET/CT in the initial WU of HNSCC provides valuable staging information with a better prognostic stratification. Patient management was modified for any disease stage, even for early stage I-II, with consequences on survival.